Pemberdayaan Lansia Melalui Edukasi Metode Balance, Eyes, Face, Arm, Speech And Time Sebagai Self Awarness Terhadap Deteksi Dini Stroke - Suyasa, I Gede Putu Darma; Agustini , Ni Luh Putu Inca Buntari; Sani, Ari Wina; Wahyuni, Ni Wayan Sri; Wangi, Ni Luh Putu Ayu Puspita; Putra, Kadek Andika Dwi (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Background: Hypertension is a common condition in primary health care, affecting approximately 25% of the adult population and more than 50% of those aged over 65 years. As the